Therapy accompanying use of VRglasses in hemiparetic children and adolescents - Jung M; Höning J (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Hemiparesis as a result of an ischemic stroke in children and adolescents under 16 years of age is reported in the literature with an incidence of approximately 3-5 and 1,6: 100.000, respectively [1,2]. If the haemorrhagic stroke and sinus thrombosis were included, the number would double. Strokes in newborns have an incidence of about 1: 2.500-4.000 newborns. Based on these causes, many children develop a (mostly spastic) partial paralysis. Physical and occupational therapy are common in the rehabilitation of hemiparesis, recognized in Germany, supplemented by a variety of (partly technical) aids. Untreated children are particularly affected by a developmental disorder, some of them never learn to walk by their own. For many years, the viewpoint of physical therapists focused very strongly on the motor component of the development. This subsequent work goes beyond this and the gain for the child is the increased participation.